Psyhological Response and Ntritional Status of Type 2 Diabetes Mellitus Patients - Rizki Andriani; Yulia Yulia; Riri Maria (School of Nursing, Faculty of Medicine, Lambung Mangkurat University., 2022)
The application of nutrient guidelines into daily menu challenges the majority of type 2 diabetes mellitus (T2DM) patients as it needs time to change their dietary habit that has been previously formed. It is common for patients to experience boredom and stress due to their diet program that has to be implemented for the rest of their lives. Psychological response has a great influence in T2DM patients in their effort to control their diet. This research aims to analyze psychological response and nutritional status, also to observe their relationship in T2DM patients. This research uses cross sectional design. It is applied on three type A hospitals in Jakarta by consecutive sampling, with 260 type 2 diabetes mellitus patients as respondents. Questionnaire is used to collect the data. There is a significantly related between psychological response and nutritional status (p = 0.000, OR =4.944) that is not influenced by confounding variable such as anti-diabetic medication, food intake, and age. Respondents with diabetes distress psychological response have 4,944 times higher risk of experiencing abnormal nutritional status compared to respondents without diabetes distress. Regular meeting is needed at least once every four weeks to fulfill psychological needs concerning diabetes.